Light scattering measurements supporting helical structures for chromatin in solution. - Campbell, A M (1978)
Laser light scattering measurements have been made on a series of polynucleosomes containing from 50 to 150 nucleosomes. Radii of gyration have been determined as a function of polynucleosome length for different ionic strength solutions. The results suggest that at low ionic strength the chromatin adopts a loosely helical structure rather than a random coil. The helix becomes more regular on increasing the ionic strength, the dimension resembling those proposed by Finch and Klug for their solenoid model.